2020
DOI: 10.3390/v12080887
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular Vesicles in Viral Replication and Pathogenesis and Their Potential Role in Therapeutic Intervention

Abstract: Extracellular vesicles (EVs) have shown their potential as a carrier of molecular information, and they have been involved in physiological functions and diseases caused by viral infections. Virus-infected cells secrete various lipid-bound vesicles, including endosome pathway-derived exosomes and microvesicles/microparticles that are released from the plasma membrane. They are released via a direct outward budding and fission of plasma membrane blebs into the extracellular space to either facilitate virus prop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 219 publications
(265 reference statements)
0
24
0
Order By: Relevance
“…They have affinity to incorporate virus-fragments, glycan components, proteins, and chunks of viral RNA [5] . EVs, depending on the proteins and genetic content they contain, play a significant role in promoting and suppressing viral infection [ 6 , 7 ]. Both EVs and viruses have the capacity to physically fuse with target cells by membrane endocytosis and incorporate nucleic acids such as RNA into host cells [7] .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…They have affinity to incorporate virus-fragments, glycan components, proteins, and chunks of viral RNA [5] . EVs, depending on the proteins and genetic content they contain, play a significant role in promoting and suppressing viral infection [ 6 , 7 ]. Both EVs and viruses have the capacity to physically fuse with target cells by membrane endocytosis and incorporate nucleic acids such as RNA into host cells [7] .…”
Section: Introductionmentioning
confidence: 99%
“…EVs, depending on the proteins and genetic content they contain, play a significant role in promoting and suppressing viral infection [ 6 , 7 ]. Both EVs and viruses have the capacity to physically fuse with target cells by membrane endocytosis and incorporate nucleic acids such as RNA into host cells [7] . In addition, EVs and viruses can illicit immune reactions and/or attenuate inflammation responses in the host [ 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…EVs are classified based on the size and biogenesis pathway. The three major classified subgroups of EVs are exosomes, microvesicles (MVs, also called microparticles), and apoptotic bodies, and their internal contents consist of lipids, proteins, and nucleic acids [ 60 , 61 ]. Exosomes, MVs, and apoptotic bodies all contain distinct proteins that indicate their biogenic pathways and specific functions [ 62 ].…”
Section: Extracellular Vesicle-based Drug Delivery Systemsmentioning
confidence: 99%
“…Indeed, application of EVs in vaccine delivery might be prospective in treatment of several types of cancers; the mechanisms, advantages, and prospects of EVs as antigen-carrier vaccines in cancer vaccine development have been previously extensively reviewed [ 31 , 32 ]. Furthermore, several studies have also reported the potential applications of EVs in vaccines against infectious diseases [ 33 , 34 ].…”
Section: Introductionmentioning
confidence: 99%